OPTIMALISASI KEUNTUNGAN PRODUKSI MAKANAN MENGGUNAKAN PEMROGRAMAN LINEAR MELALUI METODE SIMPLEKS - Tubagus Bakhrul Alam; Anggita Megasari; Ernawati Ernawati; Siti Ayu Amalia; Nenden Gustika Maulani; Isnaini Mahuda (LPPM Universitas Bina Bangsa, 2021)
Meatballs are a type of meatball that is commonly found in Indonesian cuisine. Meatballs are generally made from a mixture of ground beef and tapioca flour, but there are also meatballs made from chicken, fish, or shrimp. Although meatballs are a chinese food, but this food has been found in Indonesia and is common. Meatballs have the characteristics of each region in Indonesia and many people like it. The purpose of this study is to optimize the sales profits of fish meatballs and fish meatball crackers. To obtain maskimal benefits, the right formula is needed through production planning with linear programming. One method that can be used in linear progamming is the simplex method that serves to find the optimum solution. Linear programming is a simplex method that works to find the optimum solution. Based on the results of linear programming analysis of the amount of fish meatball production obtained optimal profit formula Z = 500,000X1 + 200,000X2. From the calculation of the simplex method it can be concluded that there is an increase in sales profit of Rp.875,000 if the production of fish meatballs against the type of fish meatballs (X2) is increased as much as the previous production amount. The difference between the profit before and after optimization amounted to Rp. 175,000